Ecophysiological responses by loess grassland vegetation to elevated air C02 concentration in a miniFACE system - Nagy, Zoltán (Acta Biologica Szegediensis, 2002)
The experiment focused on the responses by loess grassland vegetation to elevated air CO2 concentration (EC) with N as the second factor. Investigated responses include growth dynamics at stand (LAI) and at individual plant level (RGR). Leaf scale CO2/H2O gas exchange, shoot carbohydrate content, canopy surface temperatures and above ground dry matter production have also been measured. LAI has been slightly decreased by EC concentrations in both the high and low N treatments. RGR was lower in the monocots in the EC treatment than in the ambient, while similar growth depression was not found in the dicots. These results are in agreement with the dawn-evening carbohydrate pattern and CO2 gasexchange in the leaves of the same species. Canopy surface temperatures were higher during the day in the EC treatment than in the ambient with average difference of 1.5ºC. The yield has not increased in the multi-species loess stands due to EC.